Visible colorimetric dosimetry of UV and ionizing radiations by a dual-module photochromic nanocluster - Huangjie Lu (Nature Portfolio, 2021)
Radiation dosimeters that measure ionizing radiations over a broad range and allow for direct readout are desirable. Here, the authors present a dual-mode photochromic thorium-based metal-organic nanocluster that enables direct visible colorimetric dosimetry of UV, β-ray, and γ-ray radiation.